Long-term hematopoietic response in leukocyte counts and differentials for rhesus macaques (Macaca mulatta) from acute whole-body radiation exposure - Chino, Yuiko, author; Johnson, Thomas, advisor; Bailey, Susan, committee member; Kato, Takamitsu, committee member; Walrond, John, committee member (Colorado State University. Libraries, 2023)
Accumulating evidence from A-bomb survivors and radiation therapy patients suggest that survivors are at risk of developing delayed effects of acute radiation exposure (DEARE). In contrast to acute radiation syndrome (ARS), the underlying mechanisms of DEARE are largely unknown. Better understanding of DEARE is vital for improving estimates of risk and predictions of long-term health outcomes following a variety of radiation exposure scenarios, whether accidental or intentional, and including nuclear accidents, cancer treatment, and space travel. The hematopoietic system is highly sensitive to ionizing radiation (IR) exposure; leukocyte counts reach a nadir in days to several weeks post-acute exposure, followed by a recovery period from 4-8 weeks to a year. Accumulating evidence from the A-bomb survivor cohort and animal studies suggests residual damage in the hematopoietic system persists for a long time. Long-term effects in hematopoietic system are very likely the underlying cause of DEARE disease, although there is limited understanding of the process. In this study, archival leukocyte counts and differentials from the Non-Human Primate Radiation Late Effects Cohort (RLEC), were analyzed to evaluate long-term effects. The RLEC cohort consists of over 200 Rhesus Macaques (Macaca mulatta) previously exposed to acute whole body irradiation from 1.14 to 8.5 Gy and approximately 50 control animals. The dataset was created from blood sampling started approximately 1 year post-exposure and continued every 2-6 months. Linear mixed models were developed for total leukocyte count and the differentials including neutrophil, lymphocyte, and monocyte counts and their percentages. Preliminary analysis was conducted for animals with the same dose level, sex, and age at the time of exposure and age and sex matched control animals. The linear mixed models had statistically significant elevations in leukocyte and neutrophil counts and neutrophil% in irradiated animals compared to the controls. Lymphocyte% was significantly lower in irradiated animals. Longitudinal trends for both control and irradiated animals were consistent with expected trends of aging in hematopoiesis, which is skewed towards production of myeloid lineage cells such as neutrophils and monocytes rather than lymphoid cells. There was no statistical difference among the longitudinal trends of control and irradiated animals. Next analysis was extended from the preliminary analysis with a larger dataset including animals with different dose, sex, age at the time of exposure, as well as mitigator assignment. Longitudinal trends were estimated for different dose levels (control, <LD10; 1.14 to 5.5 Gy, LD10-LD50; 5.5 to 6.8 Gy, >LD50; 6.8 to 8.5 Gy), and adjusted for sex, age at the time of exposure, and status of mitigator use. All models suggested that dose levels were a statistically significant factor for the longitudinal trends of leukocytes and the differentials. Controls showed a slight decrease of total leukocyte count and monocyte skewed differentiation, consistent with changes estimated from aging in hematopoietic system. The <LD10 animals were very similar to the controls. However, estimates for LD10-50 animals demonstrated a statistically significant increase and decrease in percentages of neutrophils and lymphocytes, respectively. The increase in monocyte counts was larger for LD10-50 and >LD50 animals than controls and <LD10 animals. Elevated neutrophil and monocyte counts are indicative of inflammation status and/or a skewing of the immune system from innate to more adaptive. Long-term impairment of the immune system could contribute to DEARE disease, including cancer and cardiovascular disease, which were observed more frequently in irradiated animals. Extended analyses include developing and testing machine learning models to improve accuracy of predictions related to a number of radiation biomarkers and health outcomes, key steps toward improved understanding and risk assessment of DEARE.
Keywords: late effects of ionizing radiation; whole body irradiation; radiation biology; health physics